2013
DOI: 10.1007/s10549-013-2598-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic, mammographic, and sonographic features in 1,187 patients with pure ductal carcinoma in situ of the breast by estrogen receptor status

Abstract: Background The clinicopathologic, mammographic, and sonographic findings in patients with pure ductal carcinoma in situ (DCIS) were assessed by estrogen receptor (ER) expression. Methods After institutional review board approval, patients with pure DCIS evaluated from January 1996 to July 2009 with known ER status and available imaging were identified. Images were reviewed per the ACR BI-RADS® lexicon (4th edition). Clinical, pathologic, and imaging characteristics were analyzed by ER status using t-test, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 44 publications
2
29
0
Order By: Relevance
“…4042 There was no significant association between imaging features of microcalcifications and ER status; however, ER-negative pure DCIS was associated with high nuclear grade, comedonecrosis, and older age. 25 Therefore, ER-negative pure DCIS is more likely to be aggressive; this needs to be taken into consideration when management options are selected, especially in older women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4042 There was no significant association between imaging features of microcalcifications and ER status; however, ER-negative pure DCIS was associated with high nuclear grade, comedonecrosis, and older age. 25 Therefore, ER-negative pure DCIS is more likely to be aggressive; this needs to be taken into consideration when management options are selected, especially in older women.…”
Section: Discussionmentioning
confidence: 99%
“…This is an expansion of our previous study 25 that included only patients with known ER status; in the current study, we included 692 additional patients who did not have ER status determined.…”
Section: Methodsmentioning
confidence: 99%
“…In present case, it was also obtained a positive results for hormonal receptor both in the mucinous and in the IDC-NST component consisted with literature reports. The absence of ER and PR expression in the in situ component wasn't surprising because it had been demonstrated that highgrade DCIS, especialy comedo-type has a negative ER and PR imunostain [25,26,27]. Both biomarkers have a predictive role since patients with a positive imunostain receive treatment with trastuzumab [28].…”
Section: Discussionmentioning
confidence: 99%
“…Whether additional DCIS cases detected only with US would be clinically important remains to be seen. Although US can certainly detect both high-and low-grade DCIS (16,17), there is very little data regarding the characteristics of DCIS detected with US alone. Of the US-only-detected cancers in the ACRIN study, only 6.2% were noninvasive.…”
Section: Does More Imaging Necessarily Mean More Overdiagnosis?mentioning
confidence: 99%